2013
DOI: 10.4236/ajps.2013.42a050
|View full text |Cite
|
Sign up to set email alerts
|

Generalist <i>versus</i> Specialist Herbivores on the Invasive <i>Senecio inaequidens</i> and a Native Related Species: What Makes the Difference?

Abstract: We compared herbivory pressure in the native Jacobaea vulgaris (formely Senecio jacobaea) and the alien invasive S. inaequidens in sites where they co-occur in Belgium. We predicted that the alien species experiences relaxed herbivory pressure by specialist herbivores (enemy release hypothesis ERH) whereas it is still attacked by generalist herbivores. Impacts of two generalist (gastropods and rabbits) and one specialist (the caterpillar Tyria jacobaeae) herbivores were assessed with field observations and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The presence of alien species may, however, have positive effects on the competitive ability of native species by reducing the pressure of generalist herbivores on native species. Recent studies (Jacquemart et al, 2013 ) and meta-analyses (Parker and Hay, 2005 ; Parker et al, 2006 ) indicate that some generalists have a preference for alien plant hosts over native plants, while some alien plants may negatively impact on the survival of generalist herbivores (Tallamy et al, 2010 ), and may thus benefit native species, altering the competitive balance between alien and native species. How apparent competition may affect or interact with resource competition in determining the establishment of alien species remains unclear and requires additional investigations.…”
Section: Disentangling Resource Competition From Other Mechanismsmentioning
confidence: 99%
“…The presence of alien species may, however, have positive effects on the competitive ability of native species by reducing the pressure of generalist herbivores on native species. Recent studies (Jacquemart et al, 2013 ) and meta-analyses (Parker and Hay, 2005 ; Parker et al, 2006 ) indicate that some generalists have a preference for alien plant hosts over native plants, while some alien plants may negatively impact on the survival of generalist herbivores (Tallamy et al, 2010 ), and may thus benefit native species, altering the competitive balance between alien and native species. How apparent competition may affect or interact with resource competition in determining the establishment of alien species remains unclear and requires additional investigations.…”
Section: Disentangling Resource Competition From Other Mechanismsmentioning
confidence: 99%
“…Thus, genetic/phenotypic divergence between native and non-native populations of D. stramonium cannot be ruled out. For instance, it is likely that other toxins that may be absent in populations that lack coevolved herbivores [ 14 ] explain the differential host recognition and, hence, herbivore load on plants [ 33 ]. This suggests that compounds like HIVPs and VOCs should be compared between native and non-native plants.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Belgium showed that S. inaquidens was more prone to generalist herbivores in its introduced range compared to the related J. vulgaris, which was more susceptible to herbivory by specialist feeders (Jacquemart et al 2013). Introduced plants are suggested to be able to exhibit adaptations for increased generalist defence compared to their native conspecifics as shown for J. vulgaris populations in their introduced range (i.e.…”
mentioning
confidence: 99%
“…and has therefore been continued to be used as a model species for other Senecio spp. for insect herbivore research (Jacquemart et al 2013). Within farming, J. vulgaris is known to be toxic to livestock and can cause hepatic failure and death.…”
mentioning
confidence: 99%
See 1 more Smart Citation